2003
DOI: 10.1111/j.1365-2621.2003.tb12295.x
|View full text |Cite
|
Sign up to set email alerts
|

Starch Granule Size Strongly Determines Starch Noodle Processing and Noodle Quality

Abstract: Chemical compositions, physical properties, and suitability for starch noodle making of different granule size fractions from potato and sweet potato starches were studied. The ash content, amylose content, phosphorus content, gel firmness, and freeze-thaw stability of small-size granule fractions (< 20 m) were significantly different from those of the large-size granule fractions. The processibility and the qualities evaluated by objective and subjective methods of both dried and cooked starch noodles made fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(87 citation statements)
references
References 13 publications
4
80
0
3
Order By: Relevance
“…Fortification with ACS also resulted in very high firmness of the cooked noodles, which might be due to the preponderance of crystalline regions in ACS (Tester and Morrison 1990). Chen et al (2003b) also reported reduced firmness of SPS noodles, both in dry and cooked form, compared to the MBS noodles. The firmness of the dry and cooked noodles from 100 % SPS was 122.9 N and 0.45 N respectively, compared to the respective values of 19.69 N and 1.58 N for the Chinese sweet potato variety, Su Shu 8 (Chen et al 2003b).…”
Section: Texture Profile Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Fortification with ACS also resulted in very high firmness of the cooked noodles, which might be due to the preponderance of crystalline regions in ACS (Tester and Morrison 1990). Chen et al (2003b) also reported reduced firmness of SPS noodles, both in dry and cooked form, compared to the MBS noodles. The firmness of the dry and cooked noodles from 100 % SPS was 122.9 N and 0.45 N respectively, compared to the respective values of 19.69 N and 1.58 N for the Chinese sweet potato variety, Su Shu 8 (Chen et al 2003b).…”
Section: Texture Profile Analysismentioning
confidence: 99%
“…Chen et al (2003b) also reported reduced firmness of SPS noodles, both in dry and cooked form, compared to the MBS noodles. The firmness of the dry and cooked noodles from 100 % SPS was 122.9 N and 0.45 N respectively, compared to the respective values of 19.69 N and 1.58 N for the Chinese sweet potato variety, Su Shu 8 (Chen et al 2003b). This indicated that the cooked noodles from the present study were much softer than the Chinese noodles.…”
Section: Texture Profile Analysismentioning
confidence: 99%
“…Moreover, the use of sweet potato and products including starch is primarily determined by its physicochemical properties. Pasting behaviour, crystalline structure and gelatinization of sweet potato starches have been investigated [9][10][11]13].…”
Section: Introductionmentioning
confidence: 99%
“…The starch content of the fresh roots can vary from 6.9% to 30.7% [9]. Starch, the main industrial product of sweet potatoes is used in the manufacture of noodles [10,11], syrup, glucose and isomerized glucose [12], bakery and snack foods [1]. The carbohydrate composition in sweet potato roots greatly affects the eating quality and processing traits [13].…”
Section: Introductionmentioning
confidence: 99%
“…Rice starch is relatively small (about 2μm) while potato starches have larger granules (up to 100μm). Starch granule size affects starch digestibility properties (Dhital et al, 2010;Noda et al, 2008;Parada and Aguilera, 2009), food quality such as noodle quality (Chen et al, 2003), and potentially crop productivity (Hofvander et al, 2004). Some studies of modified potato starches via inhibition of starch biosynthetic genes have altered granule morphology and number (Edwards et al, 1995;Jobling et al, 2002;Marshall et al, 1996).…”
Section: E Granule Size and Numbermentioning
confidence: 99%